The Effect of Education to the Patient 'S Families and Nurses on the Control of Oral Mucositis in Leukemic Children Receiving Chemotherapy - ÖZDEMİR, Serap; ZÜLFİKAR, O. Bülent (Göbeklitepe Medical Science Journal, 2022)
The main purpose of this research is the leukemia in children treated with chemotherapy, the effect of education to the patient's family and caring nurse on controlling oral mucositis. The study which is semi-experimental and analytical was conducted between April-May 2011 in the pediatric hematology-oncology service of two educational-research hospital and two university hospitals in Istanbul. In this study, the sampling was carried out with the mother (34), which constitutes 95% of the universe, and the nurses (40), which constitutes %98. It was found that mothers and nurses of children with leukemia who received chemotherapy had higher post-education oral practices, oral care and mouth-protecting nutrition behaviors compared to pre education. When we evaluated the differences of point averages between before education and after education; both mother and nurses group’s 3 sub-domain and total point averages are extremely different, after education it is seen that the points are dramatically increasing. It is seen that the trainings to be given to the mothers and nurses who care in chemotherapy symptom management will contribute to the control of oral mucositis.